Religious changes and cultural transformations in the early modern western Sephardic communities - Ḳaplan, Yosef (Studies in Jewish history and culture, 2019)
Front Matter -- Copyright page -- Preface /Yosef Kaplan -- Acknowledgments -- Figures and Tables -- Notes on Contributors -- Markers of Converso Identities -- A Crisis of Judeoconverso Identity and Its Echoes, 1391 to the Present /David Graizbord -- A Family of the Nação from the Atlantic to the Mediterranean and Beyond (1497–1640) /James Nelson Novoa -- Conversos versus Recusants: Shaping the Markers of Difference (1570–1680) /Natalia Muchnik -- Richelieu in Marrano Garb: Conversos as Agents of the French Confessional Model, c. 1640 /Claude B. Stuczynski -- Semi-Clandestine Judaism in Early Modern France: European Horizons and Local Varieties of a Domestic Devotion /Carsten L. Wilke -- Prison Revelations and Jailhouse Encounters: Inquisitorial Prisons as Places of Judaizing Activism and Cross-Cultural Exchange /Ronnie Perelis -- Mechanisms of Social Discipline in the Sephardic Communities -- Defining Deviance, Negotiating Norms: Raphael Meldola in Livorno, Pisa, and Bayonne /Bernard Dov Cooperman -- A Sephardic Saga in the Dutch Republic: The Cohen Pallache Women on Love, Religion, and Social Standing /Tirtsah Levie Bernfeld -- Dispute Resolution and Kahal Kadosh Talmud Torah: Community Forum and Legal Acculturation in Eighteenth-Century Amsterdam /Evelyne Oliel-Grausz -- The “Livro de Pleitos”: The Leadership of the Spanish and Portuguese Community of London in the Eighteenth Century as a Court of Requests /Alex Kerner -- Economy and Community among Italian Sephardim -- Jews in the Papal States between Western Sephardic Diasporas and Ghettoization: A Trial in Ancona as a Case Study (1555–1563) /Serena Di Nepi -- The Sephardic Community and Social Practices in the Circuit of Money: Social Implications of Payment Networks in the Context of the Livorninas /Mauricio Dimant -- Charity Begins at Home: Reflections on the Dowry Society of Livorno /Nourit Melcer-Padon -- The Boundaries of Rabbinical Authority -- Jacob Sasportas and Problems of Discipline in the Ets Haim Yeshiva /Yaacob Dweck -- A Letter’s Importance: The Spelling of Daka(h) (Deut. 23:2) and the Broadening of Western Sephardic Rabbinic Culture /David Sclar -- Hakham Yaakov Athias—A Portuguese Rabbi Facing the Winds of Enlightenment and Secularization /Yocheved Beeri -- Varieties of Cultural Creativity -- On the Role of Hebrew Grammars in the Western European Diaspora and the New World /Moisés Orfali -- New Jews in Amsterdam: Some Social Aspects Reflected in the Thesouro dos Dinim by Menasseh ben Israel /Aliza Moreno-Goldschmidt -- Penso de la Vega and the Question of Jewish Baroque /Einat Davidi -- Crossing the Atlantic—Sephardic Communities in the New World -- Sea Is History, Sea Is Witness: The Creation of a Prosopographical Database for the Sephardic Atlantic /Michael Studemund-Halévy -- Revisiting Blackness, Slavery, and Jewishness in the Early Modern Sephardic Atlantic /Jonathan Schorsch -- Feckless Fathers, Fraught Families: Abandonment and Cultural Change in the Early Modern Jewish World /Jessica Vance Roitman -- The Gabay Dynasty: Plantation Jews of the Colonial Atlantic World /Stanley Mirvis -- Patriots at the Periphery: David Nassy, the French Revolution, and the Emancipation of the Dutch Jews /Sina Rauschenbach -- Back Matter -- Index of Names and Places.